Implementation of procedures and evaluation of data from compliance tests of Power Generating Modules of categories A1 and A2 - Bláha, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
The ever-increasing number of untested small Power Generating Modules (PGM) poses certain challenges and risks for Distribution System Operator (DSO) in the future, as these PGM have not been verified and therefore DSO cannot reliably predict their behavior, especially in extreme situations. However, to ensure reliable operation and power quality, it is necessary to require certain behavior of PGMs. This behavior is already defined, but the exact verification procedure, or rather the functional laboratory that would allow PGM compliance certification is missing. This paper deals with both the principle of testing and mainly the processing of measured data and their evaluation, along with definition of a output measurement report. The correct data processing and representation is partial task for a certified workplace, which would enable PGM testing.
Keywords: RES, PGM, PV, inverter, RfG, testing, data processing